Perilaku Keputusan Pembelian Produk Skincare Dan Kosmetik Yang Di Pengaruhi Manfaat Produk, Harga Dan Kualitas Produk - Saputra, Muhammad; Nouvan, M. Ahadi; Sari, Novita; Narasi, Iis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2024)
This study aims to determine whether product benefits, price and product quality have an effect on purchasing decisions for Skincare and cosmetic products. The type of research used is causality quantitative research. The population chosen in this study are consumers who have purchased Something products. The sampling method used in this study was nonprobability sampling using purposive sampling technique, so 170 respondents were obtained. The data analysis method used in this study is Partial Least Square (PLS). The results of the analysis state that product benefits have no effect on purchasing decisions for Skincare and cosmetic products. Price affects the decision to purchase Skincare and cosmetic products. Product quality affects the purchase decision of Skincare and cosmetic products.